Anti–racism Muslim mobilities in the San Francisco Bay Area. Issue 6 (2nd November 2021) - Itaoui, Rhonda; Dufty-Jones, Rae; Dunn, Kevin Mark
ABSTRACT: After the election of President Trump in 2016, Muslim Americans were increasingly targeted by Islamophobia in a range of spaces, restricting Muslim American mobility within and across public spaces. Yet, little is known about how Muslims actively negotiate, resist, subvert and survive their compromised mobilities. Analysis of data from twenty-eight (28) interviews conducted in 2017 in the San Francisco Bay Area, United States (US), is framed around concepts drawn from the literatures on the geographies of Islamophobia and anti-racism mobilities. We found that young Muslim Americans devised and deployed a range of anti-racism mobilities that were social, embodied, technological, and a combination of all three. We argue that the 2016 election was a key context that has worked to shape counter-mobility efforts of Muslim Americans. Such context is critical in shaping the spaces and places of counter-mobilities.